2012
DOI: 10.1515/cclm.2011.819
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thyroid peroxidase antibodies are associated with the absence of distant metastases in patients with newly diagnosed breast cancer

Abstract: TPOab occurrence is associated with significantly lower frequency of distant metastases in breast cancer. TPOab level inversely correlates with the conventional tumor markers CA-15-3 and CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…The data also suggested that lymph node involvement and hormone receptor-negative tumors (e.g., ER-negative) were also less frequent among hypothyroid patients, but this association was not statistically significant. In agreement with our study, Farahati et al (25) recently reported that the presence of TPOab is associated with a lower frequency of metastasis in breast cancer patients. However, in addition to that study, we observed that TPOab positivity may protect breast cancer patients from local recurrence or distant metastasis during the follow-up period.…”
Section: Discussionsupporting
confidence: 94%
“…The data also suggested that lymph node involvement and hormone receptor-negative tumors (e.g., ER-negative) were also less frequent among hypothyroid patients, but this association was not statistically significant. In agreement with our study, Farahati et al (25) recently reported that the presence of TPOab is associated with a lower frequency of metastasis in breast cancer patients. However, in addition to that study, we observed that TPOab positivity may protect breast cancer patients from local recurrence or distant metastasis during the follow-up period.…”
Section: Discussionsupporting
confidence: 94%
“…18,22 Many studies showed the non-significant differences between the breast cancer patients and the control group in mean serum FT3 levels. 23,24,25 The serum free thyroxine (FT4) was significantly lower in the breast cancer patients when compared to the controls (p<0.05). There was no significant difference found between the pre-treatment CA breast, the fibrocystic disease patients and the controls (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…That study differed from the current study in that they used qualitative data to determine thyroid disease, and they showed functional sensitivities for TgAb (positivity﹥60 U/ml) and TPOAb (positivity﹥60 U/ml). However, uniform positive criteria for TPOAb and TgAb have not been reported to date (Ditsch et al, 2010;Farahati et al, 2012;Szychta et al, 2013). A meta-analysis conducted in 2012 showed a confirmed relationship between AITD and BC by pooling the results of studies based on positive criteria for TPOAb and TgAb.…”
Section: Discussionmentioning
confidence: 99%